Comparative genome identification of accessory genes associated with strong biofilm formation in Vibrio parahaemolyticus. (April 2023) - Wang, Dan; Fletcher, Graham C.; Gagic, Dragana; On, Stephen L.W.; Palmer, Jon S.; Flint, Steve H.
Graphical abstract: Highlights: The persistence of Vibrio parahaemolyticus biofilm in the seafood plant may induce recurrence of pathogens and complicate hygienic treatment. Phyla of Proteobacteria and Gammaproteobacteria act as the main donor taxa for the genetic diversity of strong biofilm forming V. parahaemolyticus . Cellulose biosynthesis, rhamnose metabolic and catabolic processes, UDP-glucose processes and O antigen biosynthesis contribute to robust biofilm formation. The cellulose synthase operon consists of the genes bcsG, bcsE, bcsQ, bcsA, bcsB, bcsZ, bcsC in V. parahaemolyticus . Abstract: Vibrio parahaemolyticus biofilms on the seafood processing plant surfaces are a potential source of seafood contamination and subsequent food poisoning. Strains differ in their ability to form biofilm, but little is known about the genetic characteristics responsible for biofilm development. In this study, pangenome and comparative genome analysis of V. parahaemolyticus strains reveals genetic attributes and gene repertoire that contribute to robust biofilm formation. The study identified 136 accessory genes that were exclusively present in strong biofilm forming strains and these were functionally assigned to the Gene Ontology (GO) pathways of cellulose biosynthesis, rhamnose metabolic and catabolic processes, UDP-glucose processes and O antigen biosynthesis ( p < 0.05). Strategies of CRISPR-Cas defence and MSHA pilus-led attachment were implicated via Kyoto Encyclopedia of Genes and Genomes (KEGG) annotation. Higher levels of horizontal gene transfer (HGT) were inferred to confer more putatively novel properties on biofilm-forming V. parahaemolyticus. Furthermore, cellulose biosynthesis, a neglected potential virulence factor, was identified as being acquired from within the order Vibrionales . The cellulose synthase operons in V. parahaemolyticus were examined for their prevalence (22/138, 15.94 %) and were found to consist of the genes bcsG, bcsE, bcsQ, bcsA, bcsB, bcsZ, bcsC . This study provides insights into robust biofilm formation of V. parahaemolyticus at the genomic level and facilitates: identification of key attributes for robust biofilm formation, elucidation of biofilm formation mechanisms and development of potential targets for novel control strategies of persistent V. parahaemolyticus .